Parameterized algorithms for d - Hitting Set: The weighted case - Fernau, Henning (Theoretical computer science, 2010)
We are going to analyze search tree algorithms for Weighted d - Hitting Set. Although the algorithms that we develop are fairly simple, their analysis is technically involved. We compare the weighted case with the previously analyzed unweighted one, exhibiting that the advantage of the unweighted case dwindles with growing d .